2013
DOI: 10.1194/jlr.p036475
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diet and plasma long-chain n-3 PUFAs in older people: impact of apolipoprotein E genotype

Abstract: ( P < 0.0001), alcohol intake ( P = 0.0006), and female gender ( P = 0.02), and decreased with intensive consumption of n-6 oils ( P = 0.02). The positive association between fi sh consumption and plasma DHA was highly signifi cant whatever the APOE genotype ( P < 0.0001) but stronger in APOE4 noncarriers than in carriers ( P = 0.06 for interaction). Plasma DHA increased signifi cantly with age ( P = 0.009) in APOE4 noncarriers only. These fi ndings suggest that dietary habits, gender, and APOE4 genotype shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…[135]. Accordingly, this finding is supported by a previous report showing that plasma DHA increased significantly with age in ApoE4 non-carriers only [136]. Furthermore, it has been shown that consumption of fatty fish was associated with a reduced risk of dementia and AD in individuals without the ApoE ε4 allele [137].…”
Section: Decreases Of Amyloid Beta and Cholesterol Levelssupporting
confidence: 85%
“…[135]. Accordingly, this finding is supported by a previous report showing that plasma DHA increased significantly with age in ApoE4 non-carriers only [136]. Furthermore, it has been shown that consumption of fatty fish was associated with a reduced risk of dementia and AD in individuals without the ApoE ε4 allele [137].…”
Section: Decreases Of Amyloid Beta and Cholesterol Levelssupporting
confidence: 85%
“…40 DHA metabolism may be affected by a host of factors including age, APOE genotype, body mass index, sex, and alcohol consumption, which may explain the inconsistencies across studies. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compared to non-carriers of APOE4 (i.e. APOE2 and APOE3), consumption of n-3 PUFA, such as DHA, fails to reduce the risk of cognitive decline [5,8]. This could potentially be explained by a disturbed DHA metabolism in APOE4 carriers, supported by lower DHA content in the brain of APOE4 animals and humans [9,10].…”
Section: Introductionmentioning
confidence: 94%